Is bone mineral density in middle-aged and elderly individuals associated with their dietary patterns? A study based on NHANES - Runting, Huang; Qingyue, Luo; Yining, Yuan; Huiyu, Shu; Shu, Yang; Xixi, Feng (Frontiers in Nutrition, 2024)
Bone mineral density (BMD) is an important index for predicting fracture risk and diagnosing osteoporosis. With the worldwide epidemic of osteoporosis, understanding the relationship between dietary patterns and BMD is critical to public health. The study used data from the National Health and Nutrition Examination Survey (NHANES) to explore the relationship between dietary patterns and BMD. We analyzed 8,416 NHANES survey participants aged 40 years and older over three non-consecutive cycles from 2013 to 2020.Three different dietary patterns were identified by combining factor analysis and cluster analysis: "Low protein-High Dietary fiber-Vitamin A-Magnesium (LP-HDF-Vit A-Mg)","High macronutrient -Choline -Selenium (HM-Cho-Se)" and "Low macronutrient -Vitamin D-Calcium (LM-Vit D-Ca)". We found that women, older adults, and people of certain ethnic groups were at higher risk for low BMD. Participants who adhered to the "HM-Cho-Se" and "LP-HDF-VitA-Mg" patterns had significantly higher BMD than those who adhered to the "LM-Vit D-Ca" pattern. After adjusting for demographic variables, the "HM-Cho-Se" pattern was still positively associated with BMD. However, the "LM-Vit D-Ca" pattern was not significantly associated with BMD or the risk of suffering low BMD.This suggests that better adherence to the "HM-Cho-Se" pattern may reduce the risk of developing low BMD and also suggests that these nutrients may have potential synergies for bone health. However, there are limitations to the study, including the potential subjectivity of its cross-sectional design and factor analysis. Future studies should employ longitudinal designs, including different age groups, to better understand the causal relationship between dietary patterns and BMD. Despite these limitations, our findings highlight the importance of dietary factors in maintaining bone health and suggest potential dietary interventions to reduce the risk of low BMD and osteoporosis.